Resposta :
[tex]16\text x^2-2 = 0[/tex]
utilizando o produto notável :
[tex](\text a-\text b)(\text a+\text b) = \text a^2-\text b^2[/tex]
vamos fazer aparecê-lo na expressão :
[tex]\displaystyle 16\text x^2-2 = 0 \\\\ (4\text x)^2 - ( \sqrt{2})^2 = 0 \\\\ (4\text x-\sqrt{2})(4\text x+\sqrt{2}) = 0 \\\\ \underline{\text{ou seja}}: \\\\ 4\text x-\sqrt{2} = 0 \ \ \text{ou} \ \ 4\text x+\sqrt{2}= 0 \\\\ \underline{\text{portanto}}: \\\\ \huge\boxed{\text x= \frac{\sqrt{2}}{4} \ \ \ \ \text{ou} \ \ \ \ \text x = \frac{-\sqrt2}{4}\ }\checkmark[/tex]